PENGARUH PERMAINAN TRADISIONAL HADANG TERHADAP TINGKAT KEBUGARAN JASMANI SISWA SD NEGERI 72 KOTA BENGKULU - Ilahi, Bogy Restu (Dharmas Education Journal (DE_Journal), 2023)
This study aims to determine whether there is an increase in physical fitness through traditional games of Hadang in SD Negeri 72 Bengkulu City. In the initial observation conducted by researchers at SD Negeri 72 Bengkulu City, there was no increase in physical fitness through traditional games for students at SD Negeri 72 Bengkulu City. This study uses a quasi-experimental method and a One group pretest-posttest design. The sample of this study was the fourth and fifth grade students of SD Negeri 72 Bengkulu City,total of 48 students consisting of 27 male students and 21 female students, using purposive sampling technique. Data collection using a test, namely TKJI for ages 10 to 12 years. The results of hypothesis testing using t-test obtained "t" _"count"  of 6.093 which is greater than "t" _"table"  of 2.011 (6.093 > 2.011), so there is a significant difference in the data before and after being treated. Thus, it can be concluded that there is an influence of the traditional game of Hadang on the level of physical fitness of the fourth and fifth graders of SD Negeri 72 Bengkulu City.